PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI MADRASAH IBTIDAIYAH MUHAMMADIYAH GONDANG KABUPATEN SUKOHARJO TAHUN PELAJARAN 2021/2022 - Muhammad Wibi Alamsyah; Arif Effendi (Jurnal Inovasi Penelitian, 2022)
Muhammad Wibi Alamsyah and Arif Effendi,Thesis, The effect of Principle leadership on teacher performance at Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022, Surakarta Mamba’ul ‘Ulum of Islamic Instutute. This research wish to know the Principle leadership of Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022 ; wish to know teacher performance of Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022 ; and wish to know the correlation between the Principle leadership and teacher performance at Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022. This research is a type of correlational quantitative research that correlates two variables, Subject in this study are teacher at Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022. with a population of 9 teachers with no sample. The data analysis technique to test the hypothesis in this study is to use the Product Moment correlation analysis technique. The results showed that the Principle leadership of Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022 was in very good category ; the teacher performance of Muhammadiyah Ibtidaiyah Madrasah in Gondang regency of Sukoharjo Academic year 2021/2022 was the good category; The results of correlation are r xy = 0,873 or the category is very strong category